Condição intermitente do trabalho na área cultural e a precarização de direitos trabalhistas de fazedores de cultura - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The 2017 Labor Reform in Brazil (Law 13.467) brought about significant changes in the country's legislative landscape. This reform was enacted with the stated aim of modernizinglabor relations, stimulating economic growth, and increasing job creation. Among its main changes were the flexibilization of labor regulations, direct negotiation between employers and employees, and the expansion of the outsourcing regime. The reform generated intense debates about its social, economic, and legal impacts. While some argued that it would bring greater dynamism to the labor market and facilitate the hiring of labor, others expressed concerns about the potential precarization of working conditions and the reduction of workers’ rights. In this context, this research analyzed how the 2017 Labor Reform influenced the work activities of cultural practitioners, especially those operating in the municipality of Santarém, in western Pará. Additionally, it investigated the main impacts of the SARS-CoV-2 pandemic on the labor activities of cultural practitioners. Data collection consisted of semi-structured interviews. The interviews were conducted remotely. A flexible approach was adopted, allowing participants to express their experiences, perceptions, and challenges related to the changes in labor legislation. The collected information was subjected to content analysis. This method allowed for the identification of patterns, themes, and meanings present in the participants' accounts. The analysis was carried out systematically, aiming to understand the impacts of the labor reform and the pandemic on the lives of cultural practitioners in Santarém. The results indicated that the impacts were varied. Some cultural practitioners reported additional difficulties and precarization of working conditions, while others noted little practical change in their daily activities.
Keywords: Cultura; Fazedores de Cultura; Reforma Trabalhista; Direito do trabalho; CNPQ::CIÊNCIAS SOCIAIS APLICADAS